2018
DOI: 10.9755/ejfa.2018.v30.i5.1676
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of physiological roles, plant resources, synthesis, purification and oxidative stability of Alpha-linolenic Acid

Abstract: Alpha-linolenic acid (ALA) is a polyunsaturated fatty acid (PUFA) comprising of 18 carbon atoms and three double bonds. Because the first double bond counted from the methyl terminus, is at position three, ALA belongs to the so-called n-3 group. Derived mainly from natural plants such as Linum usitatissimum and Perilla frutescens, it is an essential fatty acid for the human body. ALA is essential for the regulation of blood lipid, blood pressure and blood sugar, for the prevention of diseases and for the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 146 publications
(175 reference statements)
0
1
0
Order By: Relevance
“…Alpha-linolenic acid (ALA) occupies a special place in the family of omega-3 acids-it is a precursor of other FAs of the omega-3 family, i.e., eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Numerous studies have demonstrated the beneficial effect of ALA in the prevention and treatment of many diseases, e.g., central nervous system disorders, cardiovascular diseases, and some types of cancer [3,20,21]. However, considering linseed oil as a source of ALA, it should be remembered that the complexity of its composition remains a controversial issue.…”
Section: Introductionmentioning
confidence: 99%
“…Alpha-linolenic acid (ALA) occupies a special place in the family of omega-3 acids-it is a precursor of other FAs of the omega-3 family, i.e., eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Numerous studies have demonstrated the beneficial effect of ALA in the prevention and treatment of many diseases, e.g., central nervous system disorders, cardiovascular diseases, and some types of cancer [3,20,21]. However, considering linseed oil as a source of ALA, it should be remembered that the complexity of its composition remains a controversial issue.…”
Section: Introductionmentioning
confidence: 99%
“…S5). (KEGG Pathway database (https://www.genome.jp/kegg/pathway.html), Ali et al, 2010;Castellarin et al, 2007b;Dong and Lin, 2021;Clifford et al, 2017;Petrussa et al, 2013;Tang YuHan et al, 2018;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%